Dynamics in the carrying capacity of Ghana’s population - Bans-Akutey, Anita (Journal of Social, Humanity, and Education, 2025)
Purpose: This study assesses the limitations of Thomas Malthus' population theory and explores how Cornucopian perspectives offer solutions to the sustainability of Ghana's population within the framework of the vicious cycle model. Research methodology: The study used existing literature to analyse historical and contemporary sources on Malthusian and Cornucopian perspectives; and applied it to the analysis of demographic data and socio-economic indicators to assess the applicability of these theories in a modern Ghanaian context. Results: The study finds that Malthus' theory is limited by its failure to anticipate technological advancements and improved agricultural practices, which have mitigated the risks of a Malthusian crisis. Cornucopian theorists provide a more optimistic view, arguing that innovation and socio-economic development can counteract the negative effects of rapid population growth. In Ghana, strategic investments in education, health, and technology have the potential to break the vicious cycle of poverty and population growth, aligning with Cornucopian ideas. Limitations: The study does not account for all local factors influencing population dynamics in Ghana. Contribution: This study contributes to the field of population studies by providing a comparative analysis of Malthusian and Cornucopian theories, with a specific focus on their relevance to contemporary issues in developing countries like Ghana. Novelty: The novelty lies in its application of classical population theories to the modern context of Ghana.